2009
DOI: 10.1093/rheumatology/kep104
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of sicca symptoms with hydroxychloroquine in patients with Sjogren's syndrome

Abstract: HCQ treatment led to a beneficial effect on xerostomia in patients with pSS who lack severe organ manifestations. The response was greater in alpha-fodrin-positive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 14 publications
0
27
1
3
Order By: Relevance
“…These similar results may be attributed to the use of HQ in pSS patients, because the alleviating effect of HQ (reducing the levels of BAFF in the tear fluid of pSS patients) has been demonstrated in a previous study (29) . In another study, the beneficial effect of HQ on xerostomia has also been demonstrated in pSS patients (30) . In this current study, although we could not measure the levels of BAFF in the serum of the participants, we postulated that the similarity between the pSS patients and healthy subjects with respect to the thickness of mGCIPL and pRNFL, except in the inferior quadrant, may have been a consequence of the reduced effects of HQ on the serum levels of BAFF in pSS patients (31) .…”
Section: Discussionmentioning
confidence: 84%
“…These similar results may be attributed to the use of HQ in pSS patients, because the alleviating effect of HQ (reducing the levels of BAFF in the tear fluid of pSS patients) has been demonstrated in a previous study (29) . In another study, the beneficial effect of HQ on xerostomia has also been demonstrated in pSS patients (30) . In this current study, although we could not measure the levels of BAFF in the serum of the participants, we postulated that the similarity between the pSS patients and healthy subjects with respect to the thickness of mGCIPL and pRNFL, except in the inferior quadrant, may have been a consequence of the reduced effects of HQ on the serum levels of BAFF in pSS patients (31) .…”
Section: Discussionmentioning
confidence: 84%
“…Improvement in xerostomia is demonstrated after 3-9 months use of HCQ in a retrospective study by Rihl et al [12]. They especially mentioned that this effect was much more prominent in a subgroup of patients with a positive a-fodrin antibody.…”
Section: Discussionmentioning
confidence: 96%
“…In another retrospective analysis of patients with pSS, HCQ was found to improve the tear and saliva production due to its antiinflammatory activity in SS patients. As a consequence, HCQ was considered to be beneficial to ameliorate the extra glanduler functions in SS patients [11]. Hydroxy chloroquine treatment was initiated in our patients diagnosed of SS, as well.…”
Section: Discussionmentioning
confidence: 94%